Further Remarks on "The Duration of the Adjustment Process of Financial Ratios" - Davis, Harry Zvi; Peles, Yoram C. (The Review of Economics and Statistics, 1992)
In a recent paper, Yoram C. Peles and Meir I. Schneller (1989) ignore the sampling autocorrelation bias. A replication of their work that removes the bias changes their results. With the bias removed, there is no evidence that their three long-term ratios follow an adjustment process. Copyright 1992 by MIT Press.